Growth and solar energy conversion in soybeans grown under four solar radiation levels - Melges, Elena; Lopes, Nei F.; Oliva, Marco A. (Pesquisa Agropecuaria Brasileira, 2014)
Growth and efficiency of solar energy conversion were studied in soybean (Glycine max (L.) Merrill) cv. UFV-2 grown under four levels (30%, 50%, 70% and 100%) of solar radiation incidence under field conditions. Plant samples were collected every 14 days regularly. Crop growth rates decreased with reduction of solar radiation, and these differences were due to reduced net assimilation rates and to smaller leaf areas presented by shaded plants. Net assimilation rate and relative growth rate declined with ontogeny as well as with reduction of solar radiation. The leaf area ration increased with shading, mainly due to variations in specific leaf area, because leaf weight ratio did not change significantly. The efficiency of solar energy conversion increased with shading and decreased with plant ontogeny. Maximum efflciencies of solar energy conversion were 1.70%, 1.65%, 1.91% and 2.26% for the 100%, 70%, 50% and 30% light treatments. The average efficiency of solar energy conversion throughout the entire crop cycle was of 0.33%, 0.48%, 0.45% and 0.59% for the decreasing light levels.